Nutritional quality and levels of acceptability of innovative fish-based products: breaded and kamaboko - Vilca-Cáceres Vilma Amalia (Journal of the Selva Andina Research Society, 2020)
The main objective of the present study is to evaluate the nutritional quality and the levels of acceptability of innovated fish-based products in the Province of Llo, Peru. The research was of an applied type. The elaboration of the products was carried out in the laboratory of fishing processes of the Professional School of Fishing Engineering of the National University of Moquegua, then the nutritional evaluation was carried out in the laboratory of the Faculty of Zootechnics of the National Agrarian University of La Molina Subsequently, the acceptability analysis was carried out in the dining room facilities of the Santa Elizabeth Educational Institution in the Llo Province, using a hedonic scale of 7-level categories as an instrument. The results show that the protein in the innovated products: breaded and kamaboko (fish paste) are present with 25.55% in breaded with bean flour, followed by breaded with banana flour with 21.94% and finally kamaboko with 20.34%. Breaded with banana flour was the one that had the highest acceptance with 86.3%, followed by kamaboko paste with 59.2%, while breaded with bean flour only obtained 26.7%. When evaluating the levels of nutritional quality and acceptability of the innovated fish-based products, it can be concluded that they have nutritional quality and a high level of acceptance, especially the breaded with banana flour and kamaboko paste.